2018
DOI: 10.30621/jbachs.2018.412
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Out-Patient Care Educational Environment of National Defence University, Malaysia utilizing the ACLEEM Inventory

Abstract: Purpose: A friendly educational environment is required for optimal learning, and students should be asked to provide feedback on their experiences to improve curriculum. Moreover, students' academic progress, mental growth, and physical well-being are influenced by the educational and clinical environment of the institute. Essential constituents of the educational climate include atmosphere, number of proper teaching-learning sessions and available amenities. Primary health care and ambulatory settings allow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
2
0
1
Order By: Relevance
“…Respondents in the study had similarities with those in other studies involving students. Earlier studies at UPNM reported more male respondents than female 104,105. However, although in the current study there were more female respondents than males, there was no statistically significant difference between genders.…”
Section: Discussioncontrasting
confidence: 92%
“…Respondents in the study had similarities with those in other studies involving students. Earlier studies at UPNM reported more male respondents than female 104,105. However, although in the current study there were more female respondents than males, there was no statistically significant difference between genders.…”
Section: Discussioncontrasting
confidence: 92%
“…The current study response rate can therefore be considered good. In the current study, there was a slightly higher number of male respondents, again, similar to earlier studies [72,73] but dissimilar to other Malaysian medical survey studies [75,76]. The context being a Malaysian military medical school most likely influenced the gender balance due to a high number of cadet officers.…”
Section: Discussionsupporting
confidence: 82%
“…The current study response rate was 99.03%. A similar high response rate was also reported in earlier studies [72,73]. The American Journal of Pharmaceutical Education reported that in “survey research intended to represent all schools and colleges of pharmacy, a response rate of ≥80% is expected” [74].…”
Section: Discussionsupporting
confidence: 80%